The evolution of latitudinal ranges in reef‐associated fishes: Heritability, limits and inverse Rapoport's rule. (24th May 2021) - Pie, Marcio R.; Divieso, Raquel; Caron, Fernanda S.; Siqueira, Alexandre C.; Barneche, Diego R.; Luiz, Osmar J.
Abstract: Aim: Variation in the size and position of geographical ranges is a key variable that underlies most biogeographical patterns. However, relatively little is known in terms of general principles driving their evolution, particularly in the marine realm. In this study we explore several fundamental properties regarding the evolution of reef fish latitudinal ranges, namely the degree of similarity in range size between ancestor and descendant lineages (i.e. phylogenetic signal); the evolution of range limits; and the latitudinal distribution of range sizes, particularly with respect to Rapoport's rule. Location: Global. Taxon: Reef‐associated fishes. Methods: We integrate data on the latitudinal distribution and evolutionary history of 5, 071 reef fish species with phylogenetic comparative methods to assess the level of phylogenetic signal in latitudinal range size, low‐ and high‐latitude limits and range midpoints, and to estimate rates of evolution of those traits. Finally, we test whether latitudinal ranges become smaller near the equator, as predicted by Rapoport's rule, using phylogenetic generalized least squares. Results: There were varying levels of phylogenetic signal in latitudinal range size, low‐ and high‐latitude limits and range midpoints. Despite these differences, latitudinal midpoints were consistently shown to have the highest phylogenetic signal among all measured geographical features. Interestingly, the position of high‐latitude limits in general evolved at substantially faster rates than their low‐latitude counterparts. Finally, we confirm for the first time the existence of an inverse Rapoport's rule in reef‐associated fishes using phylogenetic comparative methods. Indeed, mean latitudinal range size of tropical species is nearly twice the size of their temperate counterparts (2, 067 ± 1, 431 km vs. 1, 168 ± 725 km respectively). Main conclusions: We uncovered several congruent patterns in phylogenetic signal and rates of evolution of latitudinal ranges, despite vastly disparate biogeographical distributions and ecological differences between the studied fish lineages. Such broad congruence across different taxa and oceans, as well as with previous data from terrestrial environments, suggests that the observed patterns might represent general principles governing geographical range evolution.